Tinjauan Ulang Living Hadis dan Living Sunnah: Pemaknaan dan Eksistensi - Nuzuliyah, Wilda Rahmatin (Journal of Hadith Studies, 2022)
This article aims to review the meaning of living hadith and living sunnah as explained by M. Khairil Anwar in the article "Living Hadith" and the article "Living Sunnah: Method of Understanding the Living Sunnah" written by Romdloni. By using library research, this article intends to use both articles as primary sources. The results show that in his article, Anwar does not emphasize the difference in meaning between living hadith and living sunnah, only that Anwar slightly mentions that the study of living hadith began to attract attention after a seminar was held with the theme, "Living Qur'an: Al-Qur'an as a Socio-Cultural Phenomenon", which was organized by FKMTHI (Indonesian Hadith Interpretation Student Communication Forum) at UIN Sunan Kalijaga Yogyakarta on March 13-15, 2005. Romdloni defines living sunnah as a study that is closer to the matan area, an area that is still relatively new in the discourse of Islamic studies.